Inflammation and autonomic balance in cirrhosis: Association between sympathetic nervous system and osteopontin, interleukin‐22, interleukin‐6 and interleukin‐1Ra concentrations according to portal hypertension and disease severity - Giuseppe Miceli; Grazia Pennisi; Luisa Agnello; Vincenza Calvaruso; Emanuele Amodio; Alessandra Casuccio; Chiara Pintus; Maria Grazia Basso; Rosaria Maria Pipitone; Mario Daidone; Rossella Zito; Giulia Lupo; et al. (Wiley, 2023)
Abstract Background The autonomic nervous system is linked to hyperdynamic circulation in cirrhosis and several studies have highlighted the crucial role that systemic inflammation elicits in altering sympathovagal equilibrium with the consequent reduction in heart rate variability (HRV). To investigate the correlation between time‐domain HRV parameters, serum cytokines concentrations and portal hypertension, we studied a cohort of patients with cirrhosis, accounting for etiology and treatments. Methods In this cross‐sectional, observational cohort study, 107 outpatients with non‐alcoholic cirrhosis were assessed consecutively by abdominal ultrasound and by upper gastrointestinal endoscopy to search for esophagogastric varices. 24‐h electrocardiogram Holter monitoring with time‐domain HRV measurement (square root of the mean of successive differences of Normal‐to‐Normal [NN] [RMSSD], standard deviation or the square root of variance [SDNN] and standard deviation of the means of the NN intervals calculated over a 5‐min period [SDANN]) was performed and serum concentrations of osteopontin (OPN), interleukin (IL)‐22, IL‐6, IL‐1Ra and IL‐17 were obtained in all patients. Results IL‐6, OPN, IL‐22 and IL‐1Ra concentrations in cirrhotic patients were associated with disease severity expressed by Child‐Pugh and MELD score, to some portal hypertension's indirect signs and some of its complications. A significant increase in systemic concentrations of OPN in patients with hepatocellular carcinoma was encountered. SDANN and SDNN values were indirectly related to serum levels of IL‐6, OPN, IL‐1Ra and IL‐22. Conclusions This study underlines the interaction between the alteration of the ANS and the activation of inflammatory pathways that characterize cirrhosis taking into account clinical characteristics and treatments.